2012
DOI: 10.1007/s11357-012-9424-8
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong environmental enrichment in rats: impact on emotional behavior, spatial memory vividness, and cholinergic neurons over the lifespan

Abstract: We assessed lifelong environmental enrichment effects on possible age-related modifications in emotional behaviors, spatial memory acquisition, retrieval of recent and remote spatial memory, and cholinergic forebrain systems. At the age of 1 month, Long-Evans female rats were placed in standard or enriched rearing conditions and tested after 3 (young), 12 (middle-aged), or 24 (aged)months. Environmental enrichment decreased the reactivity to stressful situations regardless of age. In the water maze test, it de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 73 publications
3
21
1
2
Order By: Relevance
“…In our EE design, we hypothesize that 6-7 weeks of EE exposure to running wheel could have played a role in the female better cognitive performance. Our EE exposed females (future mothers) did not show modifications in anxiety-related behaviour in the EPM; literature studies show contrasting results in anxiety revealing tests (see introduction, [11][12][13][14][15][16][17]). …”
Section: Females Before Matingcontrasting
confidence: 43%
See 1 more Smart Citation
“…In our EE design, we hypothesize that 6-7 weeks of EE exposure to running wheel could have played a role in the female better cognitive performance. Our EE exposed females (future mothers) did not show modifications in anxiety-related behaviour in the EPM; literature studies show contrasting results in anxiety revealing tests (see introduction, [11][12][13][14][15][16][17]). …”
Section: Females Before Matingcontrasting
confidence: 43%
“…Much less investigated are the effects of EE on female rats. Only two studies show that enrichment in adulthood [14] or during pregnancy and lactation [49] does not induce significant changes of learning in the MWM. It is necessary to specify that in both studies, enrichment implied the inclusion of toys and various objects within the cage with the omission of a running wheel, thereby depriving animals of physical exercise.…”
Section: Females Before Matingmentioning
confidence: 99%
“…Only a few studies have assessed whether enrichment has an impact on remote memory. Enrichment was shown to enhance long-term memory for object recognition (i.e., 48 h after exposure) in both young (Bruel-Jungerman et al 2005;Leger et al 2015) and aged rats (Leal-Galicia et al 2008), and our team has previously shown that long-life environmental enrichment protects young and middle-aged rats against spontaneous forgetting (Harati et al 2013). The results of the present study extend these findings by showing that late enrichment also enables aged rats to form memory traces that are less sensitive to degradation.…”
Section: Spatial Memory Is Impaired In Aged Rats Housed In Standard Csupporting
confidence: 83%
“…Some of these studies also reported further decline following these ages (e.g., Bizon et al 2009;McQuail and Nicolle 2015). In Long-Evans female rats, previous cross-sectional studies by our team also showed impaired performance at 15 mo when compared with 6-mo-old subjects (Harati et al 2013), and further degradation of spatial reference memory between the age of 13-15 mo and 25-27 mo (Harati et al 2011(Harati et al , 2013. However, several studies highlighted the fact that the age-related decline in spatial memory reported in studies comparing age-groups concerns only some of the subjects (e.g., Gallagher et al 1993;McQuail and Nicolle 2015).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation